Perlakuan Orang Tua Pada Pembentukan Kepribadian Siswa - Eneng Nurmaharani Andari; Helmia Tasti Adri; Megan Asri Humaira (AL - KAFF: JURNAL SOSIAL HUMANIORA, 2022)
The purpose of this research is to find out the relationship between parental treatment and personalityformation for fifth grade elementary school students for the 2018/2019 academic year. This study has problem formulations and hypotheses which are formulated based on parental treatment to shape students' personalities. This research is a quantitative study using a correlational method. The subjects used in this study were the fifth grade students of SDN 1 Parakansalak with a total of 40 students. Retrieval of data in thisstudy using a questionnaire in the form of a scale as a means of collecting data. Researchers use product moment research, this research is tested for validity first, this validity uses expert judgment. Then the researchers tested the normality using lillifors, after that the reliability was tested using the Cronbach Alpha technique. The results of this study showed that there was no relationship between the treatment of parents and the formation of student personality, this result can be seen through the results of the correlation coefficient of 0.099 with a very weak level of relationship, then the coefficient of determination has a relationship of only 1%, other results as well. shown in the tcount significance value of 0.612 it can be said that H0 is accepted and Ha is rejected. The results of all tests show that there is no relationship between the treatment of parents and the formation of student personality in grade V SD. Keywords:Treatment of parents, Formation of studentpersonality